(untitled) (IITM Journal of Business Studies, 2024)
As the world becomes green, it emphasizes the importance of adopting a sustainable, environmentally and socially beneficial lifestyle. A growing body of academic research on “going green” offers a new standpoint on the concept of Green Entrepreneurship. Green entrepreneurship aims to follow classic entrepreneurial ideals while providing additional benefits to society and the environment at the same time. The study explores the influence of factors, namely, entrepreneurial creativity, university green entrepreneurial support, green recognition, and green value variables, on green entrepreneurial intentions, along with the moderating role of gender, family income and family occupation among students. Data from 600 Undergraduate and Postgraduate students was collected using the survey method. For this purpose, a structured questionnaire with a five-point Likert scale was used. The statistical techniques applied to the dataset were confirmatory factor analysis and structural equation modeling using SPSS, AMOS, and process-Macro. The results revealed that all the study variables positively and significantly influence students’ green entrepreneurial intention. Moreover, demographic factors also influence this relationship. Most of the previously conducted research focuses on entrepreneurship in context with its contribution to economic growth, development of the economy, employment generation, and reduction in a disparity of income. However, less research highlighted the green aspect of entrepreneurship and its contribution to sustainability. Moreover, there is a shortage of studies conducted to understand students’ perspectives on green entrepreneurship. The present study has attempted to realize determinants that influence green entrepreneurial intentions among UG and PG students. The study’s findings will provide directions to policymakers, entrepreneurs, students, Educational Institutions, and society to understand the ecosystem of green entrepreneurship.